P-223 Patient and carer portal. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Middleton, Nick; Smith, Matt
Abstract : The Patient and Carer Portal is a multi-layered secure website that is being developed to enable professionals and patients to access our electronic patient records. Key stakeholders will also be able to access tele-health and educational information and content through the online platform. Innovative Technology: This portal is just one of the ways technology can be used to reach out to more people, and allow us to spread the already stretched funding a little bit further. Once launched, the platform will continue to grow and help us reach patients in their own homes, where they can receive tele-health services and add notes directly into their own patient record. Reaching more patients, now and in the future: A number of additional features will be released in stages over the next few years, slowly growing the service to reach out to more people and services. This will include the ability to self-refer, and for professionals to refer online 24 hours a day, 7 days a week, 365 days a year. Tailored to Individuals: In addition to providing patients and professionals with remote access to medical records thus allowing them to read notes and directly update the records themselves - 'prescribed' information, specifically tailored to the individual patient, will also be available through the Portal. Educational Content: Instructional videos for patients and professionals will also be accessible through the portal. Examples include: therapeutic audio/visual services and content, developed in-house by our highly experienced and professional therapies team (i.e., a self-help video on 'How to deal with breathlessness').